Preservation of the qualitative properties in the vertical advection-diffusion DEM sub-model of the air pollution process - Elshebli, M.A.T. (Інститут програмних систем НАН України, 2006)
The analysis of the transport of air pollutants is one of the most widely investigated problems and it has great practical importance. The operator splitting method is a widely used tool for the solution of such problems. Because the numerical model has to preserve the main qualitative properties of the original model, we need such methods which preserve them as well. In this paper we investigate this question by use of the operator splitting approach.